Heat acclimation improves intermittent sprinting in the heat but additional pre-cooling offers no further ergogenic effect - Castle, P.; Mackenzie, R. W.; Maxwell, N.; Webborn, A. D. J.; Watt, P. W. (Journal of Sports Sciences, 2011)
The aim of this study was to determine the effect of 10 days of heat acclimation with and without pre-cooling on intermittent sprint exercise performance in the heat. Eight males completed three intermittent cycling sprint protocols before and after 10 days of heat acclimation. Before acclimation, one sprint protocol was conducted in control conditions (21.8 ± 2.2°C, 42.8 ± 6.7% relative humidity) and two sprint protocols in hot, humid conditions (33.3 ± 0.6°C, 52.2 ± 6.8% relative humidity) in a randomized order. One hot, humid condition was preceded by 20 min of thigh pre-cooling with ice packs (-16.2 ± 4.5°C). After heat acclimation, the two hot, humid sprint protocols were repeated. Before heat acclimation, peak power output declined in the heat (P < 0.05) but pre-cooling prevented this. Ten days of heat acclimation reduced resting rectal temperature from 37.8 ± 0.3°C to 37.4 ± 0.3°C (P < 0.01). When acclimated, peak power output increased by 2% (P < 0.05, main effect) and no reductions in individual sprint peak power output were observed. Additional pre-cooling offered no further ergogenic effect. Unacclimated athletes competing in the heat should pre-cool to prevent reductions in peak power output, but heat acclimate for an increased peak power output.